Identification of New Biological Pathways Involved in Skin Aging From the Analysis of French Women Genome-Wide Data - Rahmouni, Myriam; Laville, Vincent; Spadoni, Jean-Louis; Jdid, Randa; Eckhart, Leopold; Gruber, Florian; Labib, Taoufik; Coulonges, Cedric; Carpentier, Wassila; Latreille, Julie; Morizot, Frederique; Tschachler, Erwin; et al. (Frontiers in Genetics, 2022)
Skin aging is an ineluctable process leading to a progressive loss of tissue integrity and is characterized by various outcomes such as wrinkling or sagging. Researchers have identified impacting environmental factors (sun exposure, smoking, etc..) and several molecular mechanisms leading to skin aging. We have previously performed genome wide association studies (GWAS) in 502 very-well characterized French women, looking for associations with four major outcomes of skin aging, namely photoaging, solar lentigines, wrinkling, and sagging, and this has led to new insights into the molecular mechanisms of skin aging. Since individual SNP associations in GWAS explain only a small fraction of the genetic impact in complex polygenic phenotypes, we have made the integration of these genotypes into the reference Kegg biological pathways and looked for associations by the Gene Set Enrichment Analysis (GSEA) approach. 160 pathways were tested for association with the four outcomes of skin aging. This biological pathway analysis revealed new relevant pathways and genes, some likely specific of skin aging such as the WNT7B and PRKCA genes in the “melanogenesis” pathway, some likely involved in global aging such as the DDB1 gene in the “nucleotide excision repair” pathway, not picked up in the previously published GWAS. Overall, our results suggest that the four outcomes of skin aging possess specific molecular mechanisms such as "proteasome" and "mTOR signaling pathway" but may also share common molecular mechanisms such as "nucleotide excision repair".